Paracetamol use in pregnancy: Not as safe as we may think? - Katinka Nilsen; Anne Cathrine Staff; Stine Kleppe Krogsrud (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Paracetamol is used by more than 50% of women worldwide during pregnancy; headache representing the most frequent indication. Several studies report that long‐term exposure to paracetamol in utero is associated with adverse neurodevelopmental outcomes in children, indicating a dose–response effect. However, less or no risk is found to be associated with short‐term exposure. Paracetamol most likely crosses the placenta through passive diffusion, and there are several possible mechanisms for how paracetamol might affect fetal brain development. Although the literature suggests an association between prenatal paracetamol exposure and neurodevelopmental outcomes, the role of confounders cannot be ruled out. Consequently, as a precaution, we believe that pregnant women should be recommended ideally to only use paracetamol to treat conditions that might harm the fetus, such as severe pain or a high fever. This Comment aims to put focus on the potential fetal risks of paracetamol exposure in utero.